Laser‐Induced Colloidal Writing of Organometallic Precursor–Based Repeatable and Fast Pd–Ni Hydrogen Sensor. Issue 19 (12th August 2019) - Rahamim, Guy; Greenberg, Ehud; Rajouâ, Khalil; Favier, Frederic; Shpaisman, Hagay; Zitoun, David
Abstract: The advent of hydrogen economy brings new challenges in terms of safety and sensing with a need for fast and low‐cost monitoring of hydrogen concentration. Herein, a repeatable process for the fabrication of Pd‐based hydrogen sensor is presented. First, a room‐temperature reaction of organometallic precursors yields colloidal Pd/Ni alloyed nanoparticles. This organic solvent‐based colloidal dispersion shows stability over months even with a relatively high metal content (≈1 wt%). Then, a laser induced microbubble deposits the nanoparticles in predetermined patterns from a microdroplet dispersion that is placed on a glass slide. An optical microscope monitors the writing process while a multimeter measures the sensor's conductance, assessing the success of the fabrication process. The fabricated sensors demonstrate excellent hydrogen detection performance in terms of response time, signal stability, and detection limit down to 100 ppm of H2 in air at room temperature. Abstract : A repeatable process for the fabrication of Pd‐based hydrogen sensor is achieved through the laser writing of thin films from a colloidal Pd/Ni nanoparticles dispersion. The fabricated sensors demonstrate excellent hydrogen detection performance in terms of response time, signal stability, and detection limit down to 100 ppm of H2 in air at room temperature.